The duration of paid parental leave and cildren's scholastic performance - Qian Liu; Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2009)
We study how the duration of paid parental leave affects the accumulation of cognitive skills among children. We use a reform which extended parental leave benefits from 12 to 15 months for Swedish children born after August 1988 to evaluate the effects of prolonged parental leave on childrens test scores and grades at age 16. We show that, on average, the reform had no effect on childrens scholastic performance. However, we do find positive effects for children of well-educated mothers, a result that is robust to a number of different specifications. We find no corresponding heterogeneity relative to parental earnings or fathers education, or relative to other predictors of child perforÿmance. We find no effects on intermediate outcomes such as mothers subsequent earnÿings, child health, parental fertility, divorce rates, or the mothers mental health. Overall the results suggest positive causal interaction effects between mothers education and the amount of time mothers spend with their children. Since the institutional context is one in which the alternative is subsidized day care, the results imply that subsidizing longer parental leave spells rather than day care reinforce the relationship between matÿernal education and school outcomes.
Keywords: I21; J13; J24; 330; Maternal employment; Education; Human capital; Cognitive skills; Humankapital; Elternzeit; Kinderbetreuung; Bildungsniveau; Mütter; Kinder; Schweden